2021
DOI: 10.26434/chemrxiv-2021-zvq4t
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of an N-Terminal BRD4 Bromodomain-Targeted Degrader

Abstract: Targeted protein degradation is a powerful induced-proximity tool to control cellular concentrations of native proteins using small molecules. However, the design of selectivity in protein degradation remains challenging. In the case of Bromodomain and Extra-Terminal (BET) family proteins, BRD4 has emerged as the primary therapeutic target over other family members BRD2, 3 and T, but strategies to selectively degrade BRD4 rely on the use of pan-BET inhibitors optimized for BRD4:E3 protein-ubiquitin ligase (E3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Gadd et al showed that the BRD4 degrader MZ1 can induce protein-protein interactions with the E3 ligase leading to more stable and cooperative ternary complexes for BRD4 over other BET bromodomains. 19 While designing selective small-molecule inhibitors for class I bromodomains remains challenging, 20 forming distinct ternary complexes is a potential alternative for targeting specific members of the family. Targeted protein degradation may also be a useful therapeutic tool given that it allows the full protein to be removed through sub-stoichiometric treatment of degrader compounds in an event-driven process.…”
Section: Introductionmentioning
confidence: 99%
“…Gadd et al showed that the BRD4 degrader MZ1 can induce protein-protein interactions with the E3 ligase leading to more stable and cooperative ternary complexes for BRD4 over other BET bromodomains. 19 While designing selective small-molecule inhibitors for class I bromodomains remains challenging, 20 forming distinct ternary complexes is a potential alternative for targeting specific members of the family. Targeted protein degradation may also be a useful therapeutic tool given that it allows the full protein to be removed through sub-stoichiometric treatment of degrader compounds in an event-driven process.…”
Section: Introductionmentioning
confidence: 99%